CONSECUTIVE INTERPRETATION AS A TYPE OF ORAL TRANSLATION - Temirova N. A. (Academia Science Repository, 2023)
This paper analyzes consecutive interpretation as a type of oral translation in order to identify its basic and unique features to create methodological basis of training consecutive interpreters at universities. It compares consecutive interpretation with other types of interpretation and defines its identical and unique peculiarities.